Liquid metal / polymer composite thermal interface material with high internal emulsion structure and method of making same

CN123004071APending Publication Date: 2026-10-30ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611127903.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而现有液态金属热界面材料中液态金属的体积分数普遍难以超过70%,导致复合材料的整体导热性能难以显著提升

Benefits of technology

(1)超高填充与高导热:通过HIPE策略,首次实现了液态金属在聚合物基质中高达90 vol%的填充,所得复合材料的面外导热系数达到12.20 W·m-1·K-1。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123004071A_ABST
    Figure CN123004071A_ABST
Patent Text Reader

Abstract

The application discloses a liquid metal / polymer composite thermal interface material with high internal emulsion structure and a preparation method thereof, and belongs to the technical field of thermal interface materials. The thermal interface material comprises 70-95% of liquid metal and 5-30% of functional polymer by volume ratio. The liquid metal dispersed phase is dispersed in the form of liquid drops in the functional polymer continuous phase. The stable high internal emulsion structure is constructed between the naturally formed oxidation layer on the surface of the liquid metal liquid drop and the functional polymer through coordination. The out-of-plane thermal conductivity of the material reaches 3.0-13.0 W·m ‑1 ·K ‑1 , and the volume resistivity is maintained to be more than 10 9 Ω·m. The application realizes the stable dispersion of the liquid metal under high filling amount through coordination, and simultaneously gives the material the comprehensive performance of high thermal conductivity, electrical insulation and excellent flexibility, and is suitable for the thermal management of high-power chips and flexible electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of thermal interface materials, specifically to a liquid metal / polymer composite thermal interface material with a high internal phase emulsion structure and its preparation method. Background Technology

[0002] With the miniaturization and integration of electronic devices (especially artificial intelligence chips), their power density is constantly increasing, and the local heat flux density has exceeded 1 kW·cm². -2 On the other hand, the operating temperature of the device needs to be maintained below 85°C to ensure stable performance. This contradiction between "high heat flux density" and "low operating temperature" makes thermal management technology very important.

[0003] Thermal interface materials (TIMs) are used to fill the air gap between chips and heat sinks, improving heat dissipation efficiency by reducing interfacial thermal resistance (ITR). Therefore, high thermal conductivity is a primary requirement. Furthermore, to accommodate complex device structures and prevent electrical failures, the material must also possess good mechanical flexibility and electrical insulation. Currently, traditional thermal interface materials are generally thermally conductive filler / polymer composites. Thermally conductive fillers include ceramics (such as Al₂O₃, BN), metals (such as Ag, Cu), and carbon-based fillers (such as graphene, carbon nanotubes). However, while ceramic fillers provide insulation, they sacrifice flexibility; metal and carbon-based fillers, while improving thermal conductivity, suffer from poor electrical conductivity and flexibility. Gallium-based liquid metal fillers, due to their inherent high thermal conductivity and good flowability, are considered promising for overcoming the contradiction between thermal conductivity and mechanical flexibility inherent in traditional fillers. However, because liquid metals are inherently conductive, they must be dispersed in the polymer as tiny droplets to achieve insulation. However, the volume fraction of liquid metal in existing liquid metal thermal interface materials is generally difficult to exceed 70%, which makes it difficult to significantly improve the overall thermal conductivity of the composite material.

[0004] Therefore, preparing a thermal interface material that combines high thermal conductivity, electrical insulation, and mechanical flexibility remains a key challenge in the field of thermal management. Summary of the Invention

[0005] The present invention aims to provide a liquid metal / polymer composite thermal interface material with a high internal phase emulsion structure and its preparation method. The present invention constructs a composite structure with liquid metal as the dispersed phase and functional polymer as the continuous phase using a high internal phase emulsion (HIPE) template method. This unique structure separates the liquid metal droplets only by micron-sized polymer films, shortening the phonon transport path and forming a highly efficient heat conduction network. Furthermore, the polymer film and the oxide layer on the liquid metal surface effectively block electron transport, thus achieving ultra-high thermal conductivity while maintaining excellent electrical insulation.

[0006] This invention provides a liquid metal / polymer composite thermal interface material with a high internal phase emulsion structure. The thermal interface material has a high internal phase emulsion structure, with liquid metal as the dispersed phase and functional polymer as the continuous phase; the volume fraction of liquid metal is 70%~95%, and the volume fraction of functional polymer is 5%~30%. The liquid metal dispersed phase is dispersed in the functional polymer continuous phase in the form of droplets. The liquid metal droplets are tightly packed and squeezed and deformed into a polyhedral shape in a confined space. The functional polymer forms a polymer interface film between adjacent liquid metal droplets, separating the liquid metal droplets. An oxide layer is formed on the surface of the liquid metal droplet, and there is an interaction between the oxide layer and the functional polymer. The interaction is at least used to stabilize the liquid metal droplet in the continuous polymer phase.

[0007] The functional polymer contains functional groups that can interact with the oxide layer on the surface of the liquid metal; the volume fraction of the liquid metal is 70-95%.

[0008] Specifically, the liquid metal is a gallium-based liquid metal, including elemental gallium or an alloy of gallium with other metals; the alloy of gallium with other metals is selected from Ga... 90 In 10 Ga 80 In 20 Ga 75 0.5In 24 5. Ga 75 In 25 Ga 40 In 60 Ga 90 Sn 10 Ga 88 Sn 12 Ga 75 Sn 25 Ga 96 Zn4, Ga 95Zn5, Ga 75 In 10 Sn 15 Ga 68 0.5In 21 .5Sn 10 Ga 67 In 20 .5Sn 12 5. Ga 66 In 20 .5Sn 13 5. Ga 62 In 22 Sn 16 Ga 60 In 25 Sn 15 Ga 50 In 25 Sn 25 Ga 66.3 In 22.4 Sn 10.6 Zn 0.7 Any one or more combinations of numbers, where the numbers represent the mass fraction of the corresponding metal in the alloy.

[0009] Specifically, the interaction between the oxide layer and the functional polymer includes any one or more combinations of coordination, chemical bonding, hydrogen bonding, electrostatic interaction, and chelation.

[0010] Furthermore, the functional polymer contains at least one functional group capable of interacting with the liquid metal oxide layer, the functional group including any one or more combinations of carboxyl, thiol, hydroxyl, mercapto, amide, amino, phosphate, sulfonic acid, and silaneoxy groups. The functional polymer includes, but is not limited to, homopolymers, random copolymers, alternating copolymers, gradient copolymers, graft copolymers, block copolymers, star polymers, comb polymers, bottle brush polymers, hyperbranched polymers, dendritic polymers, or combinations thereof.

[0011] The present invention also provides a method for preparing the liquid metal / polymer composite thermal interface material as described above, characterized by comprising the following steps: Liquid metal is dispersed in an organic solvent through strong shearing to form micron-sized liquid metal droplets; The functional copolymer is dissolved in an organic solvent to form a polymer solution; The dispersion containing the liquid metal droplets is thoroughly mixed and stirred with the polymer solution, so that the polymer molecules are adsorbed onto the surface of the liquid metal droplets; The mixture was concentrated to achieve a polymer concentration range of 0.5–6 wt%. The concentrated mixture is poured or coated into a film, and after the organic solvent has completely evaporated, the liquid metal / polymer composite thermal interface material with a high internal phase emulsion structure is obtained.

[0012] Furthermore, the concentration process controls the polymer mass concentration in the system to be within the range of 1 to 4 wt%.

[0013] Specifically, the out-of-plane thermal conductivity of the thermal interface material is 3.0~13.0 W·m. -1 ·K -1 Volume resistivity ≥10 9 Ω·m, Young's modulus is 2~10MPa, and elongation at break is 10%~600%.

[0014] The beneficial effects of this invention are as follows: (1) Ultra-high filling and high thermal conductivity: Through the HIPE strategy, liquid metal was filled into the polymer matrix at a rate of up to 90 vol% for the first time, and the out-of-plane thermal conductivity of the resulting composite material reached 12.20 W·m. -1 ·K -1 .

[0015] (2) Excellent electrical insulation: Even with ultra-high liquid metal filling, the volume resistivity of the composite material remains at 10. 9 Ω·m or higher, meeting the standards for insulation materials.

[0016] (3) Good mechanical properties: The material has mechanical flexibility, a Young's modulus of 5.87 MPa, and an elongation at break of 22%.

[0017] (4) Balanced Comprehensive Performance: This invention synergistically achieves three key properties—high thermal conductivity, reliable electrical insulation, and mechanical flexibility—within a single material system, providing a solution to the thermal management challenges of high-power chips and flexible electronic systems. (See attached figures for details.) Figure 1 The microstructure and elemental distribution characterization diagrams are shown for the composite material prepared in Experimental Example 1 of this invention; wherein, Figure 1 In the image, (a) is a scanning electron microscope (SEM) image, (b) is a carbon element distribution map, and (c) is a gallium element distribution map; Figure 2 The graph shows the volume resistivity test results of the composite materials prepared in Examples 1, 2 and 3 of this invention under a DC voltage of 50V. Figure 3 The graph shows the test results of the elastic modulus and elongation at break of the composite materials prepared in Examples 1, 2 and 3 of this invention; Figure 4The graph shows the test results of the interfacial thermal resistance of the composite materials prepared in Examples 1, 2 and 3 of this invention under different pressures. Figure 5 The graph shows the test results of the contact thermal resistance of the composite materials prepared in Examples 1, 2 and 3 of this invention under different pressures; Figure 6 This is a schematic diagram illustrating the application of the composite material prepared in Example 4 of the present invention in the thermal management of a 10W LED chip. Figure 7 The graph shows a comparison of the surface temperature of a 10W LED chip when the composite material prepared in Example 4 of this invention is used as a thermal interface material and when there is no thermal interface material. Detailed Implementation

[0018] The following are specific embodiments of the present invention, which further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0019] Example 1: Preparation of a thermal interface material based on 10 vol% poly(acrylate-b-styrene-b-ethyl acrylate-b-styrene) tetrablock copolymer and 90 vol% gallium-indium alloy (EGaIn). In the tetrablock copolymer, the degree of polymerization of each block is as follows: polyacrylate block 20, polystyrene block 288, polyethyl acrylate block 2397, and terminal polystyrene 288.

[0020] The present invention relates to a poly(acrylic acid-b-styrene-b-ethyl acrylate-b-styrene) tetrablock polymer, the preparation method of which can be found in “Zheqi Chen, Zipeng Ma, Jiali Tang, et al. Adaptively reconstructing network of soft elastomers to increase strand rigidity: towards free-standing electro-actuation strain over 100%[J]. Materials Horizons, 2021, 8(10):2834.”.

[0021] The specific synthesis process is as follows: The block copolymer is synthesized by RAFT emulsion polymerization mediated by amphiphilic macromolecular RAFT reagent (its structural formula is shown in the figure below).

[0022] ; First, poly(acrylate-b-styrene) seed emulsions were synthesized. A macromolecular RAFT reagent, styrene, and deionized water were mixed in a flask. The flask was purged with nitrogen at room temperature to remove oxygen, and then placed in a 70°C water bath. An aqueous solution of potassium persulfate, used as an initiator, was injected into the flask to initiate the reaction, which lasted for 90 minutes. An aqueous solution of sodium hydroxide was then slowly injected to maintain the stability of the latex, and the poly(acrylate-b-styrene) seed emulsion was collected. Next, poly(acrylate-b-styrene) seed latex, ethyl acrylate, and deionized water were mixed in a flask. Oxygen was removed again by purging with nitrogen before starting polymerization. The polymerization temperature was set at 45°C. An aqueous solution of 2,2'-azabis(2-imidazoline) dihydrochloride, used as an initiator, was injected into the flask to initiate the reaction, which lasted for 420 minutes. Third, styrene was injected into a flask to further extend the chains and form a poly(acrylic acid-b-styrene-b-ethyl acrylate-b-styrene) tetrablock polymer latex. The reaction was carried out at 45°C for 420 minutes. Finally, the resulting latex was coagulated by adding dilute hydrochloric acid aqueous solution, then the polymer was washed with deionized water until neutral, and dried in a vacuum at 120°C for 12 hours to obtain the poly(acrylic acid-b-styrene-b-ethyl acrylate-b-styrene) tetrablock polymer.

[0023] 2.79 g of EGaIn was weighed and dispersed in 25 mL of tetrahydrofuran. The solution was ultrasonicated for 2 min using a probe-type ultrasonic instrument (power: 600 W). After standing for 12 hours, the EGaIn / THF dispersion at the bottom was collected. Separately, 50 mg of the polymer was dissolved in 1 g of THF to form a polymer solution. In a fume hood at room temperature (approximately 25 °C), the two solutions were magnetically stirred for 2–6 h to evaporate the organic solvent and concentrate the mixture until the polymer concentration reached 1 wt%. Finally, the concentrated solution was poured into a mold and dried at room temperature for 12 hours to obtain a thermal interface composite film with a liquid metal content of 90 vol%. The microstructure and elemental distribution of the prepared composite material were characterized using scanning electron microscopy (SEM) and energy-dispersive spectroscopy (EDS). Figure 1 As shown (where, Figure 1 Image (a) is a scanning electron microscope image. Figure 1 (b) in the diagram is a distribution map of carbon elements. Figure 1 (c) in the diagram shows the gallium element distribution, clearly demonstrating the high internal phase emulsion structure formed at the microscopic level in the composite material prepared in this embodiment. Various performance tests were performed on the composite film prepared in this embodiment, and the results are as follows: 1) Thermal conductivity test. The results are shown in Table 1. The thermal conductivity of the composite film in this embodiment reaches 12.20 W·m. -1 ·K -‍1 It exhibits excellent thermal conductivity; 2) Volume resistivity test. Results are as follows: Figure 2 As shown, the volume resistivity of the composite thin film in this embodiment reaches 3.87. 10 9 Ω·m, achieving reliable electrical insulation; 3) Tensile test. Results are as follows: Figure 3 As shown, the composite film in this embodiment has a Young's modulus of 5.87 MPa and an elongation at break of 22%, which demonstrates the flexibility of the material. 4) Interface thermal resistance and contact thermal resistance tests. Results are as follows: Figure 4 As shown, the interfacial thermal resistance of the composite film in this embodiment, with a thickness of 300 μm, is 0.81. o C·cm 2 ·W -1 (10 psi), 0.71 o C·cm 2 ·W -1 (20psi), 0.60 o C·cm 2 ·W -1 (30 psi). Results as follows Figure 5 As shown, the contact thermal resistance of the composite film in this embodiment is 0.57. o C·cm 2 ·W -1 (10 psi), 0.46 o C·cm 2 ·W -1 (20psi), 0.35 o C·cm 2 ·W -1 (30psi). The interfacial thermal resistance and contact thermal resistance data demonstrate the excellent thermal conductivity of the composite film in this example under the application.

[0024] Example 2: Preparation of a thermal interface material based on 20 vol% poly(acrylate-b-styrene-b-ethyl acrylate-b-styrene) tetrablock polymer and 80 vol% gallium-indium alloy (EGaIn). In the tetrablock copolymer, the degree of polymerization of each block is as follows: polyacrylate block 20, polystyrene block 288, polyethyl acrylate block 2397, and terminal polystyrene 288.

[0025] 2.48 g of EGaIn was weighed and dispersed in 25 mL of tetrahydrofuran. The solution was ultrasonicated for 2 min using a probe-type ultrasonic instrument (power: 600 W). After standing for 12 hours, the EGaIn / THF dispersion at the bottom was collected. Separately, 100 mg of polymer was dissolved in 1 g of THF to form a polymer solution. In a fume hood at room temperature (approximately 25 °C), the two solutions were magnetically stirred for 2–6 h to evaporate the organic solvent and concentrate the mixture until the polymer concentration reached 4 wt%. Finally, the concentrated solution was poured into a mold and dried at room temperature for 12 hours to obtain a thermal interface material composite film with a liquid metal content of 80 vol%. Various performance tests were performed on the composite film prepared in this example, and the results are as follows: 1) Thermal conductivity test: The results are shown in Table 1. The thermal conductivity of the composite film in this embodiment reaches 5.30 W·m. -1 ·K -‍1 It exhibits excellent thermal conductivity; 2) Volume resistivity test: Results are as follows Figure 2 As shown, the volume resistivity of the composite thin film in this embodiment reaches 6.48. 10 9 Ω·m, achieving reliable electrical insulation; 3) Tensile test: Results are as follows Figure 3 As shown, the composite film in this embodiment has a Young's modulus of 6.68 MPa and an elongation at break of 240%, which demonstrates the flexibility of the material. 4) Interfacial thermal resistance and contact thermal resistance tests: Results are as follows Figure 4 As shown, the interfacial thermal resistance of the composite film in this embodiment, with a thickness of 300 μm, is 3.09. o C·cm 2 ·W -1 (10 psi), 2.63 o C·cm 2 ·W -1 (20psi), 2.10 o C·cm 2 ·W -1 (30 psi). Results as follows Figure 5 As shown, the contact thermal resistance of the composite film in this embodiment is 2.50. o C·cm 2 ·W -1 (10psi), 2.05 o C·cm 2 ·W -1 (20psi), 1.52 o C·cm 2 ·W -1(30psi). The interfacial thermal resistance and contact thermal resistance data demonstrate the excellent thermal conductivity of the composite film in this example under the application.

[0026] Example 3: Preparation of a thermal interface material based on a 30 vol% poly(acrylate-b-styrene-b-ethyl acrylate-b-styrene) tetrablock polymer and a 70 vol% gallium-indium alloy (EGaIn). In the tetrablock copolymer, the degree of polymerization of each block is as follows: polyacrylate block 20, polystyrene block 288, polyethyl acrylate block 2397, and terminal polystyrene 288.

[0027] 2.17 g of EGaIn was weighed and dispersed in 25 mL of tetrahydrofuran. The solution was ultrasonicated for 2 min using a probe-type ultrasonic instrument (power: 600 W). After standing for 12 hours, the EGaIn / THF dispersion at the bottom was collected. Separately, 150 mg of polymer was dissolved in 1 g of THF to form a polymer solution. In a fume hood at room temperature (approximately 25 °C), the two solutions were magnetically stirred for 2–6 h to evaporate the organic solvent and concentrate the mixture until the polymer concentration reached 6 wt%. Finally, the concentrated solution was poured into a mold and dried at room temperature for 12 hours to obtain a thermal interface material composite film with a liquid metal content of 70 vol%. Various performance tests were performed on the composite film prepared in this example, and the results are as follows: 1) Thermal conductivity test: The results are shown in Table 1. The thermal conductivity of the composite film in this embodiment reaches 3.41 W·m. -1 ·K -‍1 It exhibits excellent thermal conductivity; 2) Volume resistivity test: Results are as follows Figure 2 As shown, the volume resistivity of the composite thin film in this embodiment reaches 4.63. 10 10 Ω·m, achieving reliable electrical insulation; 3) Tensile test: Results are as follows Figure 3 As shown, the composite film in this embodiment has a Young's modulus of 7.18 MPa and an elongation at break of 283%, which demonstrates the flexibility of the material. 4) Interfacial thermal resistance and contact thermal resistance tests: Results are as follows Figure 4 As shown, the interfacial thermal resistance of the composite film in this embodiment, with a thickness of 300 μm, is 3.61. o C·cm 2 ·W -1 (10psi), 3.30 o C·cm 2 ·W -1 (20psi), 2.72 o C·cm 2 ·W -1(30 psi). Results as follows Figure 5 As shown, the contact thermal resistance of the composite film in this embodiment is 2.71. o C·cm 2 ·W -1 (10psi), 2.40 o C·cm 2 ·W -1 (20psi), 1.81 o C·cm 2 ·W -1 (30psi). The interfacial thermal resistance and contact thermal resistance data demonstrate the excellent thermal conductivity of the composite film in this example under the application.

[0028] Example 4: Preparation of a thermal interface material based on 20 vol% poly(acrylate-co-ethyl acrylate) copolymer and 80 vol% gallium-indium alloy (EGaIn). The copolymer has an overall average degree of polymerization of 1100, wherein the acrylic acid unit has an average degree of polymerization of 100 and the ethyl acrylate unit has an average degree of polymerization of 1000.

[0029] The poly(acrylate-co-ethyl acrylate) copolymer of this invention is prepared by referring to “Joon-Seop Kim, Yeon Hwa Nah, Soon Suck Jarng. Comparison of clustering in various acrylateionomers[J]. Polymer, 2001, 42(13): 5567.” and “Bohan Liu, Zheqi Chen, Junjie Zhao, et al. Digitally programmable microphase separation in polymer networkgenerates microstructure pattern[J]. ACS Nano, 2024, 18(50): 34353.”

[0030] The specific synthesis process is as follows: Ethyl acrylate, acrylic acid, and azobisisobutyronitrile (AIB) were dissolved in N,N-dimethylformamide. Subsequently, the dissolved oxygen in the mixture was removed by sonication for 5 minutes. The mixture was then poured into a reactor consisting of a pair of glass plates and a silicone septum. The glass plates were fixed together with adhesive clips. The entire reactor was placed in a sealed polyethylene bag. The bag was filled with nitrogen and then placed in an oven at 70°C for 13 hours. The resulting sample was placed on a hot plate at 80°C for 6 hours to evaporate the remaining monomer and N,N-dimethylformamide. 1.5 g of EGaIn was weighed and dispersed in 25 mL of tetrahydrofuran, and sonicated for 2 minutes using a probe-type sonicator (power: 600 W). After standing for 12 hours, the EGaIn / THF dispersion at the bottom was collected. Separately, 60 mg of the polymer was dissolved in 1 g of THF to form a polymer solution. In a fume hood at room temperature (approximately 25 °C), the two materials were magnetically stirred and mixed for 2–6 hours to evaporate the organic solvent and concentrate the mixture until the polymer mass concentration reached 2 wt%. Finally, the concentrated solution was coated into a film and dried at room temperature for 12 hours to obtain a thermal interface material composite film with a liquid metal content of 80 vol%. The composite film prepared in this embodiment was used as a thermal interface material in the thermal management system of a 10W LED chip, as illustrated in the schematic diagram below. Figure 6 As shown.

[0031] To evaluate the actual heat dissipation effect of the composite film, the surface temperature change of a 10W LED chip during operation was tested and compared with a control group without any thermal interface material (bare chip directly connected to a heat sink). The test results are as follows: Figure 7 As shown.

[0032] Experimental results show that after the LED chip reaches thermal equilibrium after 6 minutes of operation, the surface temperature of the control group LED chip without thermal interface material reaches as high as 48.6°C. o C; The LED chip using the composite film prepared in this embodiment as the thermal interface material exhibits a significantly reduced maximum surface temperature of 33.5°C. o C, the chip surface temperature decreased by 15.1°C. o C. This indicates that the composite material prepared in this embodiment has excellent cooling and thermal management effects in the heat dissipation of actual high-power electronic devices.

[0033] Example 5: Preparation of a thermal interface material based on 5 vol% poly(acrylate-b-styrene-b-ethyl acrylate-b-styrene) tetrablock polymer and 95 vol% gallium-indium alloy (EGaIn). In the tetrablock copolymer, the degree of polymerization of each block is as follows: polyacrylate block 20, polystyrene block 288, polyethyl acrylate block 2397, and terminal polystyrene 288.

[0034] Weigh 5.89 g of EGaIn and disperse it in 25 mL of tetrahydrofuran. Sonicate the solution for 2 min using a probe-type ultrasonic instrument (power: 600 W). After standing for 12 hours, collect the EGaIn / THF dispersion at the bottom. Separately, dissolve 50 mg of the polymer in 1 g of THF to form a polymer solution. In a fume hood at room temperature (approximately 25 °C), mix the two solutions with magnetic stirring for 2–6 h to evaporate the organic solvent and concentrate the mixture until the polymer concentration reaches 0.5 wt%. Finally, pour the concentrated solution into a mold and dry at room temperature for 12 hours to obtain a thermal interface composite film with a liquid metal content of 95 vol%.

[0035] Example 6: Preparation of a thermal interface material based on 20 vol% poly(vinylphosphonic acid-co-butyl acrylate) copolymer and 80 vol% gallium indium alloy (EGaIn). The copolymer has an overall average degree of polymerization of 630, wherein the vinylphosphonic acid unit has an average degree of polymerization of 30 and the butyl acrylate unit has an average degree of polymerization of 600.

[0036] The present invention relates to a poly(vinylphosphonic acid-co-butyl acrylate) copolymer, the preparation method of which is described in “RainerKlopsch, Marta Millaruelo, Volker Steinert, et al. Method for producing copolymers of vinylphosphonic acid[P]. Application No.: WO2008EP50704, Publication No.: WO2008090152A1, 2008-07-31.”

[0037] 2.48 g of EGaIn was weighed and dispersed in 25 mL of tetrahydrofuran. The solution was sonicated for 2 min using a probe-type ultrasonic instrument (power: 600 W). After standing for 12 hours, the EGaIn / THF dispersion at the bottom was collected. Separately, 100 mg of the polymer was dissolved in 1 g of THF to form a polymer solution. In a fume hood at room temperature (approximately 25 °C), the two solutions were magnetically stirred for 2–6 h to evaporate the organic solvent and concentrate the mixture until the polymer concentration reached 6 wt%. Finally, the concentrated solution was coated onto a film and dried at room temperature for 12 hours to obtain a thermal interface composite film with a liquid metal content of 80 vol%.

[0038] Example 7: Preparation of a thermal interface material based on 10 vol% poly(acrylamide-co-butyl acrylate) copolymer and 90 vol% gallium indium alloy (EGaIn). The copolymer has an overall average degree of polymerization of 420, wherein the acrylamide units have an average degree of polymerization of 20 and the butyl acrylate units have an average degree of polymerization of 400.

[0039] The poly(acrylamide-co-butyl acrylate) copolymer of this invention is prepared by referring to “Nianwei Yin, Keqiang Chen. Ultrasonically initiated emulsifier-free emulsion copolymerization of n-butyl acrylate and acrylamide. Part I: Polymerization mechanism[J]. Polymer, 2004, 45(11): 3587.”.

[0040] 2.79 g of EGaIn was weighed and dispersed in 25 mL of tetrahydrofuran. The solution was sonicated for 2 min using a probe-type ultrasonic instrument (power: 600 W). After standing for 12 hours, the EGaIn / THF dispersion at the bottom was collected. Separately, 50 mg of the polymer was dissolved in 1 g of THF to form a polymer solution. In a fume hood at room temperature (approximately 25 °C), the two solutions were magnetically stirred for 2–6 h to evaporate the organic solvent and concentrate the mixture until the polymer concentration reached 6 wt%. Finally, the concentrated solution was poured into a mold and dried at room temperature for 12 hours to obtain a thermal interface composite film with a liquid metal content of 90 vol%.

[0041] Example 8: Preparation of a thermal interface material based on 10 vol% poly(hydroxyethyl acrylate-b-butyl acrylate) diblock copolymer and 90 vol% gallium indium alloy (EGaIn). The degree of polymerization of each block in the diblock copolymer is as follows: 19 for the polyhydroxyethyl acrylate block and 283 for the polybutyl acrylate block.

[0042] The present invention relates to a poly(hydroxyethyl acrylate-b-butyl acrylate) diblock polymer, the preparation method of which can be found in "Andreas Mühlebach, Scott G. Gaynor, Krzysztof Matyjaszewski. Synthesis of Amphiphilic Block Copolymers by Atom Transfer Radical Polymerization (ATRP)[J]. Macromolecules, 1998, 31(18): 6046.".

[0043] 2.79 g of EGaIn was weighed and dispersed in 25 mL of tetrahydrofuran. The solution was ultrasonicated for 2 min using a probe-type ultrasonic transducer (power: 600 W). After standing for 12 hours, the EGaIn / THF dispersion at the bottom was collected. Separately, 50 mg of the polymer was dissolved in 1 g of THF to form a polymer solution. In a fume hood at room temperature (approximately 25 °C), the two solutions were magnetically stirred for 2–6 h to evaporate the organic solvent and concentrate the mixture until the polymer concentration reached 4 wt%. Finally, the concentrated solution was poured into a mold and dried at room temperature for 12 hours to obtain a thermal interface composite film with a liquid metal content of 90 vol%.

[0044] Example 9: Preparation of a thermal interface material based on 20 vol% poly(4-mercaptostyrene) polymer and 80 vol% gallium-indium alloy (EGaIn). The degree of polymerization of the poly(4-mercaptostyrene) in the polymer is 700.

[0045] The preparation method of the poly(4-thiostyrene) polymer of this invention is described in "Jincai Li, Joseph J.Richardson, Hirotaka Ejima. A Simple and Feasible Synthetic Strategy towards Poly(4-thiostyrene)[J]. Macromolecular Chemistry and Physics, 2022, 223(17):2200092."

[0046] 2.48 g of EGaIn was weighed and dispersed in 25 mL of tetrahydrofuran. The solution was sonicated for 2 min using a probe-type ultrasonic transducer (power: 600 W). After standing for 12 hours, the EGaIn / THF dispersion at the bottom was collected. Separately, 100 mg of the polymer was dissolved in 1 g of THF to form a polymer solution. In a fume hood at room temperature (approximately 25 °C), the two solutions were magnetically stirred for 2–6 h to evaporate the organic solvent and concentrate the mixture until the polymer concentration reached 5 wt%. Finally, the concentrated solution was coated onto a film and dried at room temperature for 12 hours to obtain a thermal interface composite film with a liquid metal content of 80 vol%.

[0047] Table 1 Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A liquid metal / polymer composite thermal interface material with a high internal phase emulsion structure, characterized in that, The thermal interface material has a high internal phase emulsion structure, with liquid metal as the dispersed phase and functional polymer as the continuous phase; the volume fraction of the liquid metal is 70%~95%, and the volume fraction of the functional polymer is 5%~30%. The liquid metal dispersed phase is dispersed in the functional polymer continuous phase in the form of droplets. The liquid metal droplets are tightly packed and squeezed and deformed into a polyhedral shape in a confined space. The functional polymer forms a polymer interface film between adjacent liquid metal droplets, separating the liquid metal droplets. An oxide layer is formed on the surface of the liquid metal droplet, and there is an interaction between the oxide layer and the functional polymer. The interaction is at least used to stabilize the liquid metal droplet in the continuous polymer phase. The functional polymer contains functional groups that can interact with the oxide layer on the surface of the liquid metal; the volume fraction of the liquid metal is 70-95%.

2. The liquid metal / polymer composite thermal interface material according to claim 1, characterized in that, The liquid metal is a gallium-based liquid metal, including elemental gallium or an alloy of gallium with other metals; the alloy of gallium with other metals is selected from Ga... 90 In 10 Ga 80 In 20 Ga 75 0.5In 24 5. Ga 75 In 25 Ga 40 In 60 Ga 90 Sn 10 Ga 88 Sn 12 Ga 75 Sn 25 Ga 96 Zn4, Ga 95 Zn5, Ga 75 In 10 Sn 15 Ga 68 0.5In 21 .5Sn 10 Ga 67 In 20 .5Sn 12 5. Ga 66 In 20 .5Sn 13 5. Ga 62 In 22 Sn 16 Ga 60 In 25 Sn 15 Ga 50 In 25 Sn 25 Ga 66.3 In 22.4 Sn 10.6 Zn 0.7 Any one or more combinations of numbers, where the numbers represent the mass fraction of the corresponding metal in the alloy.

3. The liquid metal / polymer composite thermal interface material according to claim 1, characterized in that, The interaction between the oxide layer and the functional polymer includes any one or more combinations of coordination, chemical bonding, hydrogen bonding, electrostatic interaction, and chelation.

4. The liquid metal / polymer composite thermal interface material according to claim 1, characterized in that, The functional polymer contains at least one functional group capable of interacting with the liquid metal oxide layer. The functional group includes any one or more combinations of carboxyl, thiol, hydroxyl, mercapto, amide, amino, phosphate, sulfonic acid, and silaneoxy groups. The functional polymer includes, but is not limited to, homopolymers, random copolymers, alternating copolymers, gradient copolymers, graft copolymers, block copolymers, star polymers, comb polymers, bottle brush polymers, hyperbranched polymers, dendritic polymers, or combinations thereof.

5. A method for preparing a liquid metal / polymer composite thermal interface material as described in any one of claims 1 to 4, characterized in that, Includes the following steps: Liquid metal is dispersed in an organic solvent through strong shearing to form micron-sized liquid metal droplets; The functional copolymer is dissolved in an organic solvent to form a polymer solution; The dispersion containing the liquid metal droplets is thoroughly mixed and stirred with the polymer solution, so that the polymer molecules are adsorbed onto the surface of the liquid metal droplets; The mixture was concentrated to achieve a polymer concentration range of 0.5–6 wt%. The concentrated mixture is poured or coated into a film, and after the organic solvent has completely evaporated, the liquid metal / polymer composite thermal interface material with a high internal phase emulsion structure is obtained.

6. The preparation method according to claim 5, characterized in that, The concentration process controls the polymer concentration in the system to be within the range of 1 to 4 wt%.

7. The liquid metal / polymer composite thermal interface material according to claim 1, characterized in that, The out-of-plane thermal conductivity of the thermal interface material is 3.0~13.0 W·m. -1 ·K -1 Volume resistivity ≥10 9 Ω·m.